Analyzing a Cost-Effectiveness Dataset: A Speech and Language Example for Clinicians - Hoch, Jeffrey S.; Haynes, Sarah C.; Hearney, Shannon M.; Dewa, Carolyn S. (Seminars in Speech and Language, 2022)
Cost-effectiveness analysis, the most common type of economic evaluation, estimates a new option's additional outcome in relation to its extra costs. This is crucial to study within the clinical setting because funding for new treatments and interventions is often linked to whether there is evidence showing they are a good use of resources. This article describes how to analyze a cost-effectiveness dataset using the framework of a net benefit regression. The process of creating estimates and characterizing uncertainty is demonstrated using a hypothetical dataset. The results are explained and illustrated using graphs commonly employed in cost-effectiveness analyses. We conclude with a call to action for researchers to do more person-level cost-effectiveness analysis to produce evidence of the value of new treatments and interventions. Researchers can utilize cost-effectiveness analysis to compare new and existing treatment mechanisms.
Keywords: net benefit regression; cost-effectiveness analysis; economic evaluation; health economics; cost–benefit analysis